2017
DOI: 10.1177/0271678x17702669
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and regenerative roles of intranasal Wnt-3a administration after focal ischemic stroke in mice

Abstract: Wnt signaling is a conserved pathway involved in expansion of neural progenitors and lineage specification during development. However, the role of Wnt signaling in the post-stroke brain has not been well-elucidated. We hypothesized that Wnt-3a would play an important role for neurogenesis and brain repair. Adult male mice were subjected to a focal ischemic stroke targeting the sensorimotor cortex. Mice that received Wnt-3a (2 µg/kg/day, 1 h after stroke and once a day for the next 2 days, intranasal delivery)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 81 publications
2
58
0
Order By: Relevance
“…In rat cerebral cortical neurons, the ANXA1-p53 interaction in the nucleus was enhanced following oxygen-glucose deprivation-reoxygenation (OGD/R) and induced cell death [40]. The Wnt signaling pathway is involved in the development of the blood-brain barrier, contributed to stimulating neurogenesis, consolidating the blood-brain structure, and recovering cognitive brain functions after central nervous system injury [41][42][43]. Chang indicated that the Gpr124-Wnt signaling axis is essential for protecting blood-brain barrier function and vascular integrity [44].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…In rat cerebral cortical neurons, the ANXA1-p53 interaction in the nucleus was enhanced following oxygen-glucose deprivation-reoxygenation (OGD/R) and induced cell death [40]. The Wnt signaling pathway is involved in the development of the blood-brain barrier, contributed to stimulating neurogenesis, consolidating the blood-brain structure, and recovering cognitive brain functions after central nervous system injury [41][42][43]. Chang indicated that the Gpr124-Wnt signaling axis is essential for protecting blood-brain barrier function and vascular integrity [44].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…On the other hand, intranasal delivery of proteins is believed to bypass the BBB in animal models [24], and our results demonstrate that this method of WNT3A delivery can produce a promising outcome on regeneration of injured brain neurons. The clinical efficacy of systemic or intranasal administration of protein drugs to the brain of TBI patients remains to be tested [25,26]. Alternatively, small-molecule activators of WNT3A, such as 6-bromoindirubin-3 -oxime (BIO), may be readily permeable to the BBB and could be considered for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…All animal experiments were approved by the Renji Hospital Institutional Animal Care and Use Committee and performed in accordance with the Institutional Guide for the Care and Use of Laboratory Animals. Focal cerebral ischemia was produced by intraluminal occlusion of the left middle cerebral artery (MCA) with a nylon monofilament suture as originally described with slight modifications . Male 2‐ to 3‐month‐old C57/B6 mice (25‐30 g each) were anesthetized with 1.5% isoflurane in a 30% O2/68.5% N2O mixture under spontaneous breathing.…”
Section: Methodsmentioning
confidence: 99%
“…Focal cerebral ischemia was produced by intraluminal occlusion of the left middle cerebral artery (MCA) with a nylon monofilament suture as originally described with slight modifications. 4,20,21 Male 2-to 3-month-old C57/B6 mice (25-30 g each) were anesthetized with 1.5% isoflurane in a 30% O2/68.5% N2O mixture under spontaneous breathing. Rectal temperature was controlled at 37°C during and after surgery via a temperature-regulated heating pad.…”
Section: Murine Model Of Transient Focal Ischemiamentioning
confidence: 99%